(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Chronic Kidney Disease (CKD) is a progressive disorder characterized by a gradual decline in kidney function, often associated with risk factors such as hypertension, diabetes, and cardiovascular diseases. Conventional treatments primarily focus on delaying disease progression through pharmacological interventions and renal replacement therapies. However, Ayurveda offers an alternative, holistic approach targeting the underlying pathophysiology through Dosha balance and lifestyle modifications. This case study evaluates the Ayurvedic management of a 32-year old male diagnosed with Grade III CKD at Jeena Sikho Lifecare Limited Clinic, Kota, Rajasthan, India. The patient presented with lumbar pain, pedal edema, and weakness. Diagnostic evaluations revealed a simple cortical cyst with cortical echogenicity. After treatment, the patient exhibited significant symptomatic relief, including reduced pedal edema and pain. Laboratory findings showed a decrease in Blood urea levels from 129.8 mg/dL to 69 mg/dL and serum creatinine levels from 8.46 mg/dL to 6.7 mg/dL. Additionally, there was a reduction in body weight from 44 kg to 40 kg, reflecting improved overall health. The results suggest that Ayurvedic therapies can enhance renal function and alleviate CKD symptoms, providing a viable complementary approach to conventional treatments. The findings highlight the potential of Ayurveda in CKD management by addressing systemic imbalances through personalized interventions. Further research is required to substantiate these observations and explore integrative treatment models that combine Ayurvedic and modern medical approaches for optimal patient outcomes.